Acquired Periungual Fibrokeratoma Resembling Koenen Tumour - Thami Gurvinder P; Kanwar Amrinder J (Wolters Kluwer Medknow Publications, 1999)
A case of periungual fibrokeratoma acquired following blunt trauma to toe, is being described. Its resemblance to koenen tumour of tuberous sclerosis and other similar lesins is discussed.